2014
DOI: 10.1130/b31113.1
|View full text |Cite
|
Sign up to set email alerts
|

The role of waterfalls and knickzones in controlling the style and pace of landscape adjustment in the western San Gabriel Mountains, California

Abstract: Bedrock rivers set the pace of landscape adjustment to tectonic and climatic forcing by transmitting signals of base-level change upstream through the channel network and ultimately to hillslopes. River incision is typically modeled as a monotonic function of bed shear stress or stream power, modulated by sediment tools and cover effects, but these models do not apply in channels with steep or vertical bedrock reaches due to changes in fl ow dynamics, hydraulic geometry, and bed cover. Here, we investigate how… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
97
1
1

Year Published

2015
2015
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 84 publications
(105 citation statements)
references
References 101 publications
(227 reference statements)
6
97
1
1
Order By: Relevance
“…For comparable situations where mean values of bedload volumes and erosion rate on bare bedrock sections are available, this model can be easily calibrated by adjusting its prefactor K. Potential applications are steep bedrock channels in detachment-starved catchments (e.g., Wohl, 1998Wohl, , 1999, channel knickpoint sections with exposed bedrock such as waterfalls (e.g., Miller, 1991;Wohl et al, 1994;Cook et al, 2013;Mackey et al, 2014;DiBiase et al, 2015), high lateral bedrock sections above the channel or its banks (e.g., Hartshorn et al, 2002;Turowski et al, 2008) or even hydropower facilities that have to cope with natural sediment flux such as sediment bypass tunnels (Jacobs and Hagmann, 2015).…”
Section: Generality Of the Resultsmentioning
confidence: 99%
“…For comparable situations where mean values of bedload volumes and erosion rate on bare bedrock sections are available, this model can be easily calibrated by adjusting its prefactor K. Potential applications are steep bedrock channels in detachment-starved catchments (e.g., Wohl, 1998Wohl, , 1999, channel knickpoint sections with exposed bedrock such as waterfalls (e.g., Miller, 1991;Wohl et al, 1994;Cook et al, 2013;Mackey et al, 2014;DiBiase et al, 2015), high lateral bedrock sections above the channel or its banks (e.g., Hartshorn et al, 2002;Turowski et al, 2008) or even hydropower facilities that have to cope with natural sediment flux such as sediment bypass tunnels (Jacobs and Hagmann, 2015).…”
Section: Generality Of the Resultsmentioning
confidence: 99%
“…All of the waterfalls occur in Mesozoic carbonate bedrock that is massive or has bedding that gently dips upstream. One possible explanation for why these steep river channel segments appear to incise less efficiently than lower-gradient channels (e.g., n < 1) is that the mechanics of river incision change when vertical waterfalls form (Lamb et al, 2007;DiBiase et al, 2015). Previous research has shown that waterfall formation may either enhance or inhibit river incision rates and would result in an apparent n > 1 or n < 1, respectively.…”
Section: Oversteepened River Channelsmentioning
confidence: 99%
“…This process can help explain why generation 2 knickpoints are not observed in basins 6-9; river channel segments have been oversteepened such that a change in rock uplift rate is insufficient to generate a new, lower knickpoint. If correct, this interpretation means that quantitative information on the timing of uplift events and uplift rates from river profiles can be obscured or erased from the river network as a result of changing incision processes due to waterfall formation (DiBiase et al, 2015).…”
Section: Oversteepened River Channelsmentioning
confidence: 99%
See 1 more Smart Citation
“…Clair et al, 2015). Given the pervasively fractured nature of bedrock in the SGM (e.g., Dibiase et al, 2015), I assume that changes in the stress state of bedrock or intact regolith near ridgetops lead to the opening of preexisting fractures (i.e., an increase in the bulk porosity of bedrock or intact regolith) rather than the fracturing of intact rock. I adopt the analytic solutions of Savage and Swolfs (1986), who solved for the topographic modification of regional compressive stresses beneath ridges and valleys oriented perpendicular to the most compressive-stress direction.…”
Section: Controls On Potential Soil Production Rates In the Sgmmentioning
confidence: 99%